Adolescent binge alcohol exposure increases risk assessment behaviors in male Wistar rats after exposure to an acute psychological stressor in adulthood. (February 2017) - Torcaso, Audrey; Asimes, AnnaDorothea; Meagher, Margaret; Pak, Toni R.
Highlights: Adolescent binge alcohol and restraint stress increased risk assessment behaviors. History of binge alcohol did not increase canonical anxiety-like behaviors. Both history of binge alcohol and restraint stress increased plasma CORT. Abstract: Teenage binge drinking is a common practice that has been shown to increase the risk for developing mood disorders in adulthood. The hypothalamo-pituitary-adrenal (HPA) axis is often dysfunctional in mood disorder patients, and animal models of adolescent binge alcohol exposure similarly show disordered HPA axis function, even after long periods of alcohol abstinence. Here, we sought to investigate the anxiety-like behavioral consequences of binge alcohol exposure in a Wistar rat model. Male rats were administered alcohol in a binge pattern during peri -puberty, and one month later, anxiety-like behaviors were measured using the elevated plus maze. A subset of the rats then underwent 30 min of restraint stress, and the anxiety-like behaviors were measured again. We observed an increase in risk assessment behaviors due to both adolescent binge alcohol exposure and restraint stress, but no differences in canonical anxiety-like behaviors. We also repeated the observation that adolescent binge alcohol induces long-term changes in HPA axis sensitivity. Therefore, we concluded that a history of peri -pubertal binge alcohol exposure subtly alters the behavioral response to subsequent acute psychological stress during adulthood, which may over time contribute to the development of mood disorders. This relatively pragmatic animal model represents a more clinically relevant tool in understanding the molecular mechanisms underlying the long-term effects of adolescent binge drinking.